MANAJEMEN KEPALA SEKOLAH DALAM PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS TIK MELALUI IN HOUSE TRAINING (IHT) BAGI GURU - Jasmiati, Jasmiati; Dewi, Silvi Listia; Aminah, Aminah (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This research aims to determine the management of school principals, obstacles to principal management and teacher responses in using ICT-based learning media through In House Training (IHT) for teachers at SD Negeri 3 Baktiya. The benefit of this research is that it becomes reference material for future research related to school principal management in the use of ICT-based learning media through In House Training (IHT), increases researchers' knowledge, especially in the field of school principal management and provides information for school principals in managing activities. utilization of ICT-based learning media through In House Training (IHT). This research uses a qualitative approach with primary data sources or subjects, namely the principal and teachers of SD Negeri 3 Baktiya and secondary data sources, namely school profile, organizational structure, teacher data and student data at SD Negeri 3 Baktiya. The data collection techniques used were observation, interviews and documentation. The data analysis techniques are data reduction, data presentation and drawing conclusions or verification. The results of this research show that school principal management in utilizing ICT-based learning media through in-house training (IHT) starts from planning, organization, implementation and supervision. Planning is tailored to teacher needs with the aim of providing teacher skills in utilizing ICT media. The organization of school principals is carried out through efficient collaboration, which distributes tasks and authority to teachers according to their competencies. The principal's implementation is carried out by providing motivation, direction and coordination. Meanwhile, supervision is carried out through observation and supervision activities. The obstacles experienced in utilizing ICT-based learning media through in-house training (IHT) at SD Negeri 3 Baktiya are the limited ability of the principal in managing activities, limited innovation development, limited instructors, limited teacher knowledge in information and communication technology operating skills. The response of SD Negeri 3 Baktiya teachers to the use of ICT-based learning media through In House Training (IHT) was very positive which was able to raise teacher motivation and feelings of joy so that skills could improve.